Artefactual serum hyperkalaemia and hypercalcaemia in essential thrombocythaemia. Issue 2 (1st February 2000) - Howard, M R; Ashwell, S; Bond, L R; Holbrook, I
Abstract : Aim —To investigate possible abnormalities of serum potassium and calcium levels in patients with essential thrombocythaemia and significant thrombocytosis. Methods —24 cases of essential thrombocythaemia with significant thrombocytosis (platelet count > 700 × 10 9 /litre) had serum potassium and calcium estimations performed at the time of maximum thrombocytosis before treatment, and at the time of low platelet count after treatment with cytoreductive drugs. Selected patients were further investigated with plasma sampling and estimation of ionised calcium and parathyroid hormone. Results —At the time of maximum thrombocytosis six patients had serum hyperkalaemia (> 5.5 mmol/litre) and five had serum hypercalcaemia (> 2.6 mmol/litre). Following treatment and reduction of the platelet count, hyperkalaemia resolved in all cases and hypercalcaemia in four of the five cases. Mean serum potassium and calcium concentrations were raised (p < 0.0001) at maximum thrombocytosis compared with the values when the platelet count was low. Serum potassium and calcium values were significantly correlated at all stages. Measurements on plasma consistently corrected the hyperkalaemia but not the hypercalcaemia. Serum hypercalcaemia was associated with raised ionised calcium and normal parathyroid hormone concentrations. Conclusions —Essential thrombocythaemia with significant thrombocytosis is associated with serum hyperkalaemia and hypercalcaemia. The probable mechanism of hypercalcaemia is the secretion of calcium in vitro from an excessive number of abnormally activated platelets. It is thus likely that the hypercalcaemia is an artefact, as is the hyperkalaemia.